2022
DOI: 10.1177/15330338221085348
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA NEAT1 Promotes the Malignant Progression of Colorectal Cancer by Targeting ZEB1 via miR-448

Abstract: Background: Long noncoding RNAs have been associated with various types of malignant tumors; however, the specific role of long noncoding RNAs in tumorigenesis still remains unclear in colorectal cancer. Here, we aim to elucidate the role of long noncoding RNA nuclear paraspeckle assembly transcript 1 in the malignant progression of colorectal cancer and investigate its underlying mechanisms. Methods: Real-time polymerase chain reaction was used to detect the expression of nuclear paraspeckle assembly transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Moreover, miR-144-3p reduces ZEB1 expression to interfere with lung cancer invasion [ 154 ]. Therefore, miRNAs and ZEB1 closely interact to regulate cancer metastasis [ 155 ].…”
Section: Circrnas Regulating Emt-tfs In Cancersmentioning
confidence: 99%
“…Moreover, miR-144-3p reduces ZEB1 expression to interfere with lung cancer invasion [ 154 ]. Therefore, miRNAs and ZEB1 closely interact to regulate cancer metastasis [ 155 ].…”
Section: Circrnas Regulating Emt-tfs In Cancersmentioning
confidence: 99%
“…The lncRNA MNX1-AS1/PPFIA4 activates the downstream AKT/HIF-1α signaling pathway to promote COAD proliferation ( 166 ). NEAT1 can regulate the miR-448/ZEB1 axis ( 167 ), and also directly acts as a molecular sponge for miR-216b, which in turn activates YY1 to promote CRC proliferation ( 168 ). PCGEM1 is elevated in CRC tissues and cells, and it regulates CRC proliferation through the miR-129-5p/SOX4 axis and the miR-433-3p/CTCF axis ( 173 , 174 ).…”
Section: Regulation Of Cell Proliferation By Lncrnasmentioning
confidence: 99%
“…Tang et al.’s study suggests that MIR497HG, as a ceRNA regulating the miR-3918/ACTG2 axis, plays a key role in CRC cell migration and invasion ( 218 ). MNX1-AS1 regulates miR-744-5p ( 165 ) or the PPFIA4/AKT/HIF-1α axis ( 166 ), playing a critical role in the invasion and migration of CRC cells.NEAT1 promotes the expression of ZEB1 by targeting miR-448 ( 167 ), or enhances the proliferation and invasion of CRC through the miR-216b/YY1 axis ( 168 ). Guan et al.…”
Section: Lncrnas Regulate Invasion and Metastasismentioning
confidence: 99%
“…For examples, lncRNA HOTAIR plays a vital role in regulation of chromatin state through interacting with polycomb repressive complex 2 [ 9 ]. In breast cancer cells, elevated expression of NEAT1 (nuclear paraspeckle assembly transcript 1) increases ZEB1 expression by sponging miR-448, thereby promoting cell growth and invasion capacity [ 10 ]. Emerging evidence has shown that lncRNAs act as “miRNA-sponges” or competing endogenous RNAs (ceRNA) to decrease the miRNA-induced repression of mRNAs [ 4 ].…”
Section: Introductionmentioning
confidence: 99%